Applications Of Taguchi Experimental Design Method In The Field Of Textile - OĞUZ, Naciye Sündüz; AKARSLAN, Feyza (International Journal of Engineering and Innovative Research, 2022)
Taguchi experimental design method is widely used in engineering field. Experiments are carried out in order to obtain the optimum values of the product designed or produced in the field of engineering. It is difficult to make the experiments because of the large number of parameters in the studies made. Therefore, with the Taguchi experimental design method, less experimentation can be done in shorter time and an accurate test strategy is being developed. Thus, saving is provided from time and cost, high quality and low cost production is achieved. In this study, information was given about Taguchi experimental design method and Taguchi applications in the field of textile.
Keywords: Engineering; Taguchi; Experimental Design; Textile; Mühendislik